A History of the Judiciary in Pakistan - Hamid Khan (Karachi Oxford University Press, 2016)
One of the major organs of the state, the judiciary in Pakistan attained a particularly high profile in recent years owing to former President Musharrafas attempt to remove the Chief Justice of Pakistan and the latteras eventual restoration to office. The exercise of suo moto jurisdiction by the Supreme Court in the matter of enforcement of fundamental rights further enhanced interest in the judiciary, which became a focal point for popular aspirations. This book undertakes a comprehensive study of judicial history in Pakistan since Independence. It includes detailed discussion of the acts, lives and judgments of important Pakistani judges, with their continuing effects on the life of the nation. Lawyers, judges and law professors and students of law, political science and history will find this book of particular value, as will the general reader.
Include Index.
Keywords: Pakistan -- Justice, Administration of -- Politics and government